Development of a banana-composite food packaging (Musa balbisiana cv. Saba) - Torralba, Aleli Charmaine C. (College of Home Economics, University of the Philippines Diliman, 2012)
Bio-based packaging from renewable resources is one of the solutions to the escalating environmental problems on plastic waste disposal. In this study, a banana-composite packaging film was developed using varying concentrations of dried banana pulp obtained from unripe banana cv. Saba, a plantain that is known to have higher starch content than dessert varieties. Compressive strength (CS) and tensile strength (TS) of the films monotically increased with increasing banana pulp concentration. Experimentally, the highest values for CS (40.9 MPa) and TS (6.8 MPa) were obtained from the films with 41% banana pulp, 40% water, 9% glycerol, 7% agar and 3% calcium carbonate. Regression analysis also showed that the amount of banana pulp was significant in predicting the CS (R2 = 0.61) and TS (R2 = 0.74). Using the prediction models, films with at least 36% banana pulp would have CS comparable to Expanded polystyrene (density=2.0). Global migration values of the films using food models were also determined. The lowest migration value with a fatty simulant was obtained in the films with 33% banana pulp which was 532.3 mg/dm2. For the aqueous simulants, the minimum values were both obtained in the films with 41% banana pulp, which were 3885.8 mg/dm2 using distilled water and 5375.8 mg/dm2 using 3% acetic acid. It was also observed that migration values using the aqueous simulants can be predicted significantly as a function of banana pulp content, using regression analysis with R2 = 0.80 for distilled water and R2 = 0.67 for 3% acetic acid. The banana composite films that were developed showed that banana has a potential to be applied as a bio-based packaging material.